Concrete-filled steel tube (CFT) truss girders: Experimental tests, analysis, and design. (1st February 2018) - Huang, Wenjin; Lai, Zhichao; Chen, Baochun; Xie, Zhitao; Varma, Amit H.
Highlights: Conducts experimental tests on CFT truss-girders. Conducts comprehensive parametric analyses using benchmarked FEM models. Evaluates the effects of brace and chord sizes and shear span-to-depth ratio. Proposes design equations for estimating the moment capacity of CFT truss girders. Abstract: This paper investigates the behavior of Warren-vertical CFT truss girders by conducting both experimental tests and finite element analyses. Experimental tests on three CFT truss girders are first conducted. The test parameter is the compressive strength of the concrete infill. Finite element models, which were developed and benchmarked previously by the authors, are then used to further investigate the behavior of CFT truss girders and the influence of parameters such as the brace-to-chord strength ratio, shear span-to-depth ratio, and concrete compressive strength. Results from the parametric studies indicate that CFT truss girders are flexure dominated if (i) the brace-to-chord strength ratio ≥0.8 and (ii) the shear span-to-depth ratio ≥4.8. Both the experimental tests and FEM analyses indicate that the concrete compressive strength has negligible effects on the failure mode of CFT truss girders. Based on results from the experimental tests and FEM analyses, design equations are also proposed for estimating the flexural strength of Warren-vertical CFT truss girders.